Dramatic Psychological Storytelling - Allen, R. author. aut Link
X, 254 p.
Keywords: This book presents a seven-step model for insight and change using the action method, Psychotheatrics, which uses the expressive arts to transform the storytelling experience into a phenomenological framework for depicting challenges, strategies and outcomes resulting in the dynamic illustration of inter-subjective meaning.